Robotic Arm Movement Optimization Using Soft Computing - Surender Kumar; Kavita Rani; V. K. Banga (Institute of Advanced Engineering and Science, 2017)
Robots are commonly used in industries due to their versatility and efficiency. Most of them operating in that stage of the manufacturing process where the maximum of robot arm movement is utilized. Therefore, the robots arm movement optimization by using several techniques is a main focus for many researchers as well as manufacturer. The robot arm optimization is This paper proposes an approach to optimal control for movement and trajectory planning of a various degree of freedom in robot using soft computing techniques. Also evaluated and show comparative analysis of various degree of freedom in robotic arm to compensate the uncertainties like movement, friction and settling time in robotic arm movement. Before optimization, requires to understand the robot's arm movement i.e. its kinematics behavior. With the help of genetic algorithms and the model joints, the robotic arm movement is optimized. The results of robotic arm movement is optimal at all possible input values, reaches the target position within the simulation time.